Cyber cafe management system - Mohammad Nur Taufiq, Ibrahim (2014)
Cyber Cafe Management System for Perbadanan Perpustakaan Awam Selangor (PPAS) is a management system to replace the manual registration system using paper form that are currently use. This system can record all the user information for the Cyber Cafe computer usage such as user's name, date and time, and floor. This sytem will include the PC monitoring system. This report consists of six (6) parts. Chapter 1 is the introduction to the project. In this part contain introduction, problem statement, objective, existing system reviews, current system and limitation and report organization. Chapter 2 is the Software Requirement Specification (SRS). In this part contain product description, interface requirements, software product features, and requirement traceability. Chapter 3 is the Software Design Document (SDD). In this part contain system overview, system states and modes, system design description, and database design. Chapter 4 presents the implementation of process that involved during development of this system.Chapter 5 presents the result obtained from the implementation phase. The constraints of system also will be discussed in this chapter. Part 6 presents the overall conclusions of the work presented in this study whether it can achieve the goal of this project.